Teologi Kebahagiaan menurut Al-Ghazali (Kajian terhadap Kitab Kimiyatus Sa’adah) - Erik Martin; Radea Yuli Ahmad Hambali (Jurnal Riset Agama, 2023)
This paper describes the concept of happiness in al-Ghazali's thought. Al-Ghazali's concept of happiness is focused on the book of chemistry al-Sa'adah which is al-Ghazali's review of happiness using a Sufism approach. The method used in this research is literature study. This type of research is included in qualitative research. The main source of this research is al-Sa'adah chemistry book by al-Ghazali. Supporting sources in this study are books on the philosophy of happiness and several related articles on happiness. The results of this study came to the conclusion that happiness in al-Ghazali's view is the achievement of cleanliness in the soul and heart. Happiness in al-Ghazali's view is not happiness based on physical or worldly. The human condition that still bases happiness on worldly things will fall into a pit of disappointment in the form of emptiness. Therefore, to achieve true happiness, humans must be able to do several things including repentance, patience, poverty, love, trust and sincerity.